A framework to assess evolutionary responses to anthropogenic light and sound. (September 2015) - Swaddle, John P.; Francis, Clinton D.; Barber, Jesse R.; Cooper, Caren B.; Kyba, Christopher C.M.; Dominoni, Davide M.; Shannon, Graeme; Aschehoug, Erik; Goodwin, Sarah E.; Kawahara, Akito Y.; Luther, David; Spoelstra, Kamiel; et al.
Highlights Anthropogenic light and sound are an important component of global change. These stimuli often co-occur and may function synergistically. The selection pressure of light and noise may drive the rate of evolutionary change. We propose a framework to explore the ultimate consequences of noise and light exposure.